2008
DOI: 10.1063/1.2828539
|View full text |Cite
|
Sign up to set email alerts
|

Theory and simulations of principle of minimum dissipation rate

Abstract: We perform a self-consistent, time-dependent numerical simulations of dissipative turbulent plasmas at a higher Lundquist number, typically up to O͑10 6 ͒, using full three-dimensional compressible magnetohydrodynamics code with a numerical resolution of 128 3 . Our simulations follow the time variation of global helicity, magnetic energy, and the dissipation rate and show that the global helicity remains approximately constant, while magnetic energy is decaying faster and the dissipation rate is decaying even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…7 in Braithwaite (2008), a selective decay of the total helicity (H) and of the magnetic energy (U Mag ) occurs during the initial relaxation with a stronger decrease in U Mag than that of H. This hierarchy, which is well known in plasma physics (see for example Biskamp 1997;Shaikh et al 2008) justifies the variational method used to derive our configuration (Montgomery & Phillips 1988) while the introduction of I I;1 is justified by the non force-free character of the field in stellar interiors (Reisenegger 2009) and by the stratification, which inhibits the transport of flux and mass in the radial direction (see Sect. 3.2 and Braithwaite 2008).…”
Section: Comparison To Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 in Braithwaite (2008), a selective decay of the total helicity (H) and of the magnetic energy (U Mag ) occurs during the initial relaxation with a stronger decrease in U Mag than that of H. This hierarchy, which is well known in plasma physics (see for example Biskamp 1997;Shaikh et al 2008) justifies the variational method used to derive our configuration (Montgomery & Phillips 1988) while the introduction of I I;1 is justified by the non force-free character of the field in stellar interiors (Reisenegger 2009) and by the stratification, which inhibits the transport of flux and mass in the radial direction (see Sect. 3.2 and Braithwaite 2008).…”
Section: Comparison To Numerical Simulationsmentioning
confidence: 99%
“…∇×B αB). Some non force-free relaxed states have been identified in plasma physics (Montgomery & Phillips 1988Dasgupta et al 2002;Shaikh et al 2008) and should be studied in a stellar context in a near future.…”
Section: Fossil Fields Barotropic Relaxation Statesmentioning
confidence: 99%
“…In the same way, we can show that dR/dt $ À 2 2 /S 2 ð Þ P k k 4 b 2 k goes at a much faster rate that dK/dt. Furthermore, a recent 3D time-dependent simulation of MHD fluids proves this argument (Shaikh et al 2008). It is shown that the energy dissipation rate, R j 2 dV , decays the fastest toward a minimum state.…”
Section: Heuristic Justification Of the Mdrmentioning
confidence: 81%
“…Rather, it is a consequence of the identification of the relaxed structures with minima of the dissipated (viscous + Joule) power. In turn, we have invoked the results of [5], generalized the results of [16], [22], [25], [40] and [41] and shown that the latter identification follows from the structure of Ohm's law and of the viscous stress tensor in our low-β, Λ ≫ 1, weakly dissipative plasma near the Sun. The proof holds for vanishing temperature gradient only, but can easily be generalized to the case of self-similar evolution [2] [13].…”
Section: Discussionmentioning
confidence: 99%